ROMANS FROM THE VIEWPOINT OF LINGUOCULTUROLOGY (Scientific journal of the Fergana State University, 2023)
The article deals with the analysis of the meaning of symbols, the symbolic world in linguistics. At the present stage of development of linguistic thought, it is believed that linguistic material is a self-sufficient and, perhaps, the most significant source of information about the world and about the person in it. A.I. Smirnitsky believed that the meaning of a word is “a well-known reflection of an object, phenomenon or relationship in the mind ... included in the structure of the word as its so-called inner side, in relation to which the sound of the word acts as a material shell”.